Buds and Blossoms: a book about flowers - Blackaby, Susan (Minneapolis Picture Window Books, 2003)
Flower features - Shades and shapes - Insects, birds, and nectar - How pollen gets around - How seeds begin to grow - Bugs and our planet - First class flowers - Fun facts
1 - 6
Keywords: Flowers; Plants; Growing Things Series